2018
DOI: 10.3847/1538-4357/aac6ed
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at an Old Cluster: The Membership, Rotation, and Magnetic Activity of Low-mass Stars in the 1.3 Gyr Old Open Cluster NGC 752

Abstract: The nearby open cluster NGC 752 presents a rare opportunity to study stellar properties at ages >1 Gyr. However, constructing a membership catalog for it is challenging; most surveys have been limited to identifying its giants and dwarf members earlier than mid-K. We supplement past membership catalogs with candidates selected with updated photometric and proper-motion criteria, generating a list of 258 members, a >50% increase over previous catalogs. Using a Bayesian framework to fit MESA Isochrones & Stellar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 84 publications
7
86
1
Order By: Relevance
“…Barnes et al (2016) found that rotation periods of M67 members delineate a sequence in the CPD reminiscent of that discovered first in the Hyades cluster. Similar sequence we can see in the mass-period diagram (which is equivalent to CPD) of NGC 752 (Agüeros et al 2018). In general, the rotational evolution theory is described in Barnes (2010), van Saders et al (2019.…”
Section: Colour-magnitude and Colour-period Diagramssupporting
confidence: 74%
“…Barnes et al (2016) found that rotation periods of M67 members delineate a sequence in the CPD reminiscent of that discovered first in the Hyades cluster. Similar sequence we can see in the mass-period diagram (which is equivalent to CPD) of NGC 752 (Agüeros et al 2018). In general, the rotational evolution theory is described in Barnes (2010), van Saders et al (2019.…”
Section: Colour-magnitude and Colour-period Diagramssupporting
confidence: 74%
“…At the age of Praesepe (580 Myr), the fit to the observed dispersion is very good down to 0.4 M , but the models fail to reproduce the short rotation period of the less massive stars. This discrepancy between models predictions and observations has been discussed in Agüeros et al (2018) and appears at the mass transition where the star remains fully convective. For these very low-mass stars, our braking prescription is too efficient and/or happens too early.…”
Section: Surface Rotation -Comparison To Observationsmentioning
confidence: 89%
“…The cluster ages reported in Fig. 7 are taken from the literature 7 , and the masses for the sample stars are from Gallet & Bouvier (2013); Bouvier et al (2014); Douglas et al (2016Douglas et al ( , 2017; Agüeros et al (2018) and references therein. The ages of the youngest clusters (up to hPer) are relatively uncertain with sometimes a factor of two uncertainty depending on the sets of isochrones used to fit their color-magnitude diagram (CMD).…”
Section: Cluster Age Uncertaintiesmentioning
confidence: 99%
“…There are also theoretical models that pair stellar evolution with a magnetic torque law to predict angular momentum evolution (e.g., van Saders & Pinsonneault 2013;Matt et al 2015;Gallet & Bouvier 2015). However, no model has been published that can explain all of the cluster rotation data (see Curtis et al 2019;Douglas et al 2019;Agüeros et al 2018). Instead, we suggest that the best way to constrain the age of the Psc-Eri stream with gyrochronology is by comparing its P rot distribution directly to the distributions measured for benchmark clusters.…”
Section: A Gyrochronological Agementioning
confidence: 99%